Manifestations of thalamic infarction - สิทธิพงษ์, สิริอนงค์; ชุติเนตร, อรอุมา (Journal of Thai Stroke Society, 2019)
Thalamus is located superiorly to the midbrain and is the relay station of multiple signals between brainstem and cerebral cortex. Thalamic blood supply comes from the posterior circulation system which composed of 4 major vessels (1) tuberothalamic artery, (2) paramedian artery, (3) thalamogeniculate artery, and (4) posterior choroidal artery. Clinical syndrome of thalamus are varies such as the abnormality of sensation, motor, neuropsychiatric symptoms, mood, autonomic system, and consciousness. There are many causes of thalamic lesion including vascular, infection, inflammation, and tumor. This topic is focused on thalamic infarction that commonly found in patients with ischemic stroke from posterior circulation.